Are Fetuin-A levels beneficial for estimating timing of sepsis occurrence? - Altınışık, Hatice Betül; Altınışık, Uğur; Uysal, Sema; Saçar, Suzan; Şimsek, Tuncer; Demiraran, Yavuz (Saudi Medical Journal, 2018)
Objectives: To evaluated Fetuin-A levels of patients admitted in the intensive care unit with a diagnosis of sepsis. Methods: This study was conducted at the Faculty of Medicine, Canakkale Onsekiz Mart University Hospital, Canakkal, Turkey, between February 2015 and October 2015. Forty septic patients were included in the study. Subsequent to clinical suspicion of sepsis, serum levels of C-reactive protein (CRP) and procalcitonin; and white blood cell (WBC) counts were evaluated at 3 time-points: 0 (basal), 24, and 72 hours. Results: The mean Fetuin-A levels at the 3 time-points were 58.5 +/- 29.2 ng/mL, 40.9 +/- 23.6 ng/mL, and 47.8 +/- 25.7 ng/mL, respectively. Fetuin-A levels at 24 hours were significantly lower than the basal level (p<0.05), where as no significant difference was observed between the basal levels and those at 72 hours (p>0.05). Correlation between the temporal changes in Fetuin-A levels and the changes in other inflammatory markers (CRP, procalcitonin and WBC) was examined. Fetuin A was found to have only a negative correlation with serum procalcitonin level (p<0.05). Conclusion: In this study, serum Fetuin-A levels in septic patients decreased significantly in the first 24 hours, followed by an insignificant increase at 72 hours. These findings suggest that monitoring of Fetuin-A levels may help predict the time of occurrence of sepsis and prognosis of sepsis.
WOS: 000452509700005
PubMed ID: 29968890
Keywords: Levels Beneficial; Estimating Timing; Sepsis